2000
DOI: 10.5488/cmp.3.2.285
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Nonequilibrium Statistics and Applications to Fermi-Bose Systems

Abstract: The aim of this work is the study of a special class of nonequilibrium systems which admits to find exact stationary solutions of the kinetic equations. In particular we investigate canonical-dissipative systems, where the driving terms are determined by the Hamiltonian or other invariants of motion only. We construct systems which drive the system to special invariants of motion and solve the corresponding Fokker-Planck equations. Finally several applications to mean-field problems for fermion and for boson s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…With regard to our subsequent discussion of relativistic Brownian motions, it will be important to keep in mind that the nonlinear Langevin equations like Eq. (5b) provide a tool for constructing Brownian motion processes with arbitrary stationary velocity and momentum distributions [19,425].…”
Section: Einstein Fluctuation-dissipation Relationmentioning
confidence: 99%
“…With regard to our subsequent discussion of relativistic Brownian motions, it will be important to keep in mind that the nonlinear Langevin equations like Eq. (5b) provide a tool for constructing Brownian motion processes with arbitrary stationary velocity and momentum distributions [19,425].…”
Section: Einstein Fluctuation-dissipation Relationmentioning
confidence: 99%
“…In general, these systems can be defined by the non-holonomic constraint, which is suggested in [11]. (2) The Fermi-Bose canonical-dissipative systems [13] which are defined by the distribution functions in the form…”
Section: Definitionmentioning
confidence: 99%
“…then we have the canonical non-Hamiltonian systems, which are considered in [12,13]. These systems are called canonical dissipative systems.…”
Section: Non-canonical Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the concept of canonical-dissipative systems has been developed to address self-propagating systems, self-excited systems, and in particular limitcycle oscillators that are supplied by energy sources [1][2][3][4][5]. Several studies have demonstrated that the canonical-dissipative approach can yield helpful insights into this kind of open systems [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%